Influence of green tea extract in the color of composite resin restorations - Lopes, R. G. [UNESP]; Oliveira-Reis, B. [UNESP]; Maluly-Proni, A. T. [UNESP]; Silva, M. H.T. [UNESP]; Briso, A. L.F. [UNESP]; dos Santos, P. H. [UNESP] (Elsevier, 2019)
The aim of this study was to evaluate the color change of composite resin restorations in Class I cavity preparation with different depths, submitted to challenge of thermocycling in coffee, after the use of green tea extract (EGCG) as treatment on the dentin surface. Forty-eight human molars were divided into 6 groups according to dentin treatment and depth of restoration (n = 8): Group C3- Control/3 mm; Group C4- Control/4 mm; Group C5- Control/5 mm; Group EGCG3- EGCG/3 mm; Group EGCG4- EGCG/4 mm; and Group EGCG5- EGCG/5 mm. The teeth of the control groups were restored by the bulk fill technique (Filtek Bulk Fill), conditioning the dentin surface only with universal bonding system (Single Bond Universal). The teeth of the EGCG groups were also restored by the bulk filling technique, but conditioning the dentin surface with 0.5% EGCG for 30 s prior to the application of the adhesive system. Initial and final color readings were performed according to the CIE L*a*b* scale in UV-2450 spectroscope, before and after challenge of thermal cycling in coffee. The color change (ΔE) was then calculated based on the formula ΔE = [(ΔL*)2+(Δa*)2+(Δb*)2]½. The ΔE data were submitted to statistical tests of normality, two-way ANOVA and Tukey test to compare the means (p < 0.05). There was no statistically difference for both study factors analyzed (EGCG application and restoration depth), as well as the interaction between both, after aging in coffee (p > 0.05). It was concluded that the previous application of EGCG did not cause a significant color change at the dentin-resin interface.
Keywords: Composite resins; Dentin; Tea